Achalasia: current treatment options. (December 2015) - Familiari, Pietro; Greco, Santi; Volkanovska, Ance; Gigante, Giovanni; Cali, Anna; Boškoski, Ivo; Costamagna, Guido
Abstract : Achalasia is a rare esophageal motility disorder, characterized by impaired swallow-induced, lower esophageal sphincter (LES) relaxation and defective esophageal peristalsis. Unfortunately, there are no etiological therapies for achalasia. Patients present with dysphagia, chest pain and regurgitation of undigested food, often leading to weight loss. The currently available treatments have the common aim of relieving symptoms by decreasing the pressure of the LES. This can be achieved with some medications, by inhibiting the cholinergic innervation (botulinum toxin), by stretching (endoscopic dilation) or cutting (surgery) the LES. Recently, other therapeutic options, including per-oral endoscopic myotomy have been developed and are gaining international consensus. The authors report on the benefits and weaknesses of the different therapies and provide an updated approach to the management of achalasia.